The Authority Of The Local Government Of The City Of Samarinda In Giving License To Open State Land (Study on Samarinda City Regional Regulation Number 2 of 2019 concerning Land Clearing Permits (IMTN) in Samarinda City) - Fachriza Fachriza; Moh. Fadli; Supriyadi Supriyadi (Budapest International Research and Critics University, 2022)
This article is entitled